2004
DOI: 10.1104/pp.103.037192
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional 3,5-Epimerase/4-Keto Reductase for Nucleotide-Rhamnose Synthesis in Arabidopsis

Abstract: L-Rhamnose is a component of plant cell wall pectic polysaccharides, diverse secondary metabolites, and some glycoproteins. The biosynthesis of the activated nucleotide-sugar form(s) of rhamnose utilized by the various rhamnosyltransferases is still elusive, and no plant enzymes involved in their synthesis have been purified. In contrast, two genes (rmlC and rmlD) have been identified in bacteria and shown to encode a 3,5-epimerase and a 4-keto reductase that together convert dTDP-4-keto-6-deoxy-Glc to dTDP-b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
75
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 49 publications
7
75
0
Order By: Relevance
“…A complete understanding of pectin function requires knowledge of pectin biosynthetic enzymes and their corresponding genes. Although the enzyme activities of proteins encoded by some pectin biosynthetic genes, particularly those involved in the synthesis of sugar nucleotides, have been elucidated (5)(6)(7)(8)(9), the activities of putative pectin biosynthetic glycosyltransferases [e.g., QUA1 (10) and NpGUT1 (11)] have not been definitively demonstrated.…”
mentioning
confidence: 99%
“…A complete understanding of pectin function requires knowledge of pectin biosynthetic enzymes and their corresponding genes. Although the enzyme activities of proteins encoded by some pectin biosynthetic genes, particularly those involved in the synthesis of sugar nucleotides, have been elucidated (5)(6)(7)(8)(9), the activities of putative pectin biosynthetic glycosyltransferases [e.g., QUA1 (10) and NpGUT1 (11)] have not been definitively demonstrated.…”
mentioning
confidence: 99%
“…The M. grisea homolog shares 37% amino acid sequence identity to a functional bacterial rmlB, dTDP-Glc 4,6-dehydratase (25,26), from Salmonella, Streptococcus, and 42% identity to the N-terminal portion of plant URS, Rhm (supplemental Fig. S3A) (18,19). Such sequence identity was not sufficient to establish the function of the gene or determine whether the encoded protein utilizes dTDP-Glc or UDP-Glc.…”
Section: Resultsmentioning
confidence: 99%
“…A bi-functional 3,5-epimerase and 4-reductase (U4k6dG-ER) converts U4k6dG to UDP-Rha and NADP ϩ . In plants (18,19) one enzyme has 4,6-dehydratase, 3,5-epimerase, and 4-reductase activities to convert UDP-Glc to UDP-Rha.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…55 Furthermore this list included NRS/ER, a gene which shows strong similarity to RHM2 but lacks one of its domains and is thus likely to be involved in the synthesis of UDP-L-rhamnose as well. 56 In addition, the model contained AtNST-KT1 (At4g39390), a gene which represents a monospecific nucleotide sugar transporter. 57 Specifically it was shown that this transporter exchanges UDP-Gal for UMP and is localized to Golgi membranes.…”
Section: Prediction Of Candidate Genesmentioning
confidence: 99%